A Cross-Domain Service Function Chain Deployment Scheme Based on Bargaining Game. (22nd January 2021) - Li, Guoyan; Ren, Yajuan; Liu, Yi
Abstract : Software-defined networking (SDN) and network function virtualization (NFV) technologies provide support for service function chain (SFC) deployment. As the scale of a network expands, SDN domains are maintained and managed by their respective network operators. When deploying an SFC in multiple domains, to protect the privacy of each domain is challenging. We propose a cross-domain SFC deployment scheme based on a bargaining game. We establish an effective cross-domain service chain system model and combine resource consumption cost and load balance to translate SFC deployment to an optimization problem. A bargaining game model is established so as to reasonably optimize these contradictory parameters. We solve the model by an improved imperialist competition algorithm and obtain the optimal node mapping relationship. Experimental results show that our method performs better than the current one in terms of network load balancing and mapping overhead and has better scalability.